Digitalization of Education in the Implementation of Kurikulum Merdeka - Novita, Mega; Dwi Saputro, Nugroho; Singh Chauhan, Alok; Waliyansyah, Rahmat Robi (KnE Social Sciences, 2022)
The Indonesian Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) recently released several educational platforms like Merdeka Belajar, Rapor Pendidikan, Belajar.id, ARKAS, TanyaBOS, SiPLah and Kampus Merdeka to make a leap in educational progress. However, the user percentage is still low, which may be due to various reasons such as limited internet access and reluctance to learn new technology. Discussion on which priority technology platforms are and how they are used to support Kurikulum Merdeka’s implementation has been limited. Therefore, this paper will analyze the primary educational platforms useful for the implementation of Kurikulum Merdeka. We carried out a systematic review of the relevant databases on the digitalization of education in implementing Kurikulum Merdeka. Although the current educational platforms are still being developed, they provide unique features which facilitate students, teachers, administrators, and principals in the learningmanagement process at all levels of education. This work has the potential to become an essential reference that provides guidelines for using the educational platform to improve the number of users. Keywords: Kurikulum Merdeka; Merdeka Belajar; software; digital school; application